Prácticas sociales frente al patrimonio cultural en Ambalema, Tolima (2017)
This article investigates the social practices of different actors in the historic city center of the municipality of Ambalema, declared as an Asset of Cultural Interest, aiming to recognize how they make use of the urban architectural heritage in order to formulate proposals that would contribute not only to the conservation and safeguarding of patrimonial assets, but also to the improvement of living conditions in the community. Through surveys, focus groups, and in-depth interviews, the inhabitants and different members of the local community were asked about their practices, seeking to understand the social significance of the accelerated deterioration of some of the representative properties in the municipality. The research concluded that conservation work carried out by different actors rarely goes beyond basic efforts, such as general maintenance and local repairs, evidencing a general tendency to passivity regarding the preservation of this asset of cultural interest.